2003
DOI: 10.1023/b:agen.0000011802.81320.e4
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on the anti-angiogenic potential of pomegranate fractions in vitro and in vivo

Abstract: We previously showed pomegranate seed oil and fermented juice polyphenols to retard oxidation and prostaglandin synthesis, to inhibit breast cancer cell proliferation and invasion, and to promote breast cancer cell apoptosis. Here we evaluated the anti-angiogenic potential of these materials in several ways. We checked a possible effect on angiogenic regulation by measuring vascular endothelial growth factor (VEGF), interleukin-4 (IL-4) and migration inhibitory factor (MIF) in the conditioned media of estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 32 publications
2
63
0
6
Order By: Relevance
“…Pomegranate juice and extracts have been shown to have potent in vitro antioxidant [7,24] and in vivo anti-atherosclerotic properties [8,9,15], attributed to its high content of polyphenols including ETs and EA. Recently, there have also been numerous reports on the in vitro and in vivo anticancer properties of pomegranates [10,[25][26][27][28][29][30]. The major pomegranate ET, punicalagin, is reported as the active ingredient responsible for N 50% of the juice's antioxidative potential [7,24] and can reach levels of N2 g/L of juice [7].…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate juice and extracts have been shown to have potent in vitro antioxidant [7,24] and in vivo anti-atherosclerotic properties [8,9,15], attributed to its high content of polyphenols including ETs and EA. Recently, there have also been numerous reports on the in vitro and in vivo anticancer properties of pomegranates [10,[25][26][27][28][29][30]. The major pomegranate ET, punicalagin, is reported as the active ingredient responsible for N 50% of the juice's antioxidative potential [7,24] and can reach levels of N2 g/L of juice [7].…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate polyphenols are potent antioxidants which have been shown both in vitro and in vivo to inhibit the growth of prostate and some other forms of cancer [10][11][12][13][14][15]. Our group has demonstrated that 8 ounces of pomegranate juice consumed daily following primary treatment of prostate cancer significantly prolonged prostate specific antigen (PSA) doubling time from 15 months to 54 months [30].…”
Section: Discussionmentioning
confidence: 99%
“…Sample RNA content was quantified by measuring the absorbance at 260 nm with a Gene Quant Spectrophotometer (Amersham-Pharmacia Biotech, Piscataway, NJ). Reverse transcription was performed on 3 ÎŒg of RNA by using oligo(dT) [12][13][14][15][16][17][18] primers (Invitrogen) with SuperScript III Reverse Transcriptase (Invitrogen) according to the manufacturer's instruction.…”
Section: Rna Extraction and Reverse Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns dos trabalhos demonstraram que o suco do fruto da P. granatum alĂ©m de retardar a oxidação e a sĂ­ntese de prostaglandinas, pode inibir a proliferação de cĂ©lulas tumorais, reduzir a invasĂŁo tumoral, promover a apoptose e ainda inibir a formação de vasos no modelo in vitro da membrana corioalantĂłide (Toi et al, 2003).…”
Section: Introductionunclassified